2010
DOI: 10.1002/bdrb.20275
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A: developmental toxicity from early prenatal exposurea

Abstract: Bisphenol A (BPA) exposure has been documented in pregnant women, but consequences for development are not yet widely studied in human populations. This review presents research on the consequences for offspring of BPA exposure during pregnancy. Extensive work in laboratory rodents has evaluated survival and growth of the conceptus, interference with embryonic programs of development, morphological sex differentiation, sex differentiation of the brain and behavior, immune responsiveness, and mechanism of actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 146 publications
(204 reference statements)
0
44
0
1
Order By: Relevance
“…In female rats, AGDs can in some cases also be affected by exposure to endocrine disruptors. In most studies of anti-androgenic exposure, female AGDs have not been affected , Christiansen et al 2009); however, androgen exposure has been shown to increase female AGD (Ostby & Gray 2001) and exposure to oestrogenic agents like ethinyl estradiol (EE 2 ) and genistein have been shown to increase or decrease female AGDs, depending on study design (Levy et al 1995, Casanova et al 1999, Delclos et al 2009, Golub et al 2010, Mandrup et al 2013). Due to the shallow dose-response curves observed in this study, it was evaluated whether unusually high control values could have caused the observed statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…In female rats, AGDs can in some cases also be affected by exposure to endocrine disruptors. In most studies of anti-androgenic exposure, female AGDs have not been affected , Christiansen et al 2009); however, androgen exposure has been shown to increase female AGD (Ostby & Gray 2001) and exposure to oestrogenic agents like ethinyl estradiol (EE 2 ) and genistein have been shown to increase or decrease female AGDs, depending on study design (Levy et al 1995, Casanova et al 1999, Delclos et al 2009, Golub et al 2010, Mandrup et al 2013). Due to the shallow dose-response curves observed in this study, it was evaluated whether unusually high control values could have caused the observed statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Also, urinary levels of BPA correlate significantly with obesity levels in a large Chinese cohort, highlighting worldwide impact. Animal studies suggest that in utero and early postnatal exposure to BPA produce a broad range of adverse effects (10)(11)(12). Historically, endocrine-reproductive and immune function-related abnormalities were documented first, and impaired brain development and behavior have been linked to BPA exposure more recently (13)(14)(15).…”
mentioning
confidence: 99%
“…Exposure of ewes to BPA at levels similar to that seen in human maternal circulation resulted in low birth weight (Savabieasfahani et al 2006). BPA-induced prenatal development perturbations in rodents, such as interference with embryonic programs of development, morphological sex differentiation, sex differentiation of the brain and behavior, immune responsiveness (Golub et al 2010), defective uterine environment, and embryonic implantation (Varayoud et al 2011), raise the question of the impact of exposure to BPA during pregnancy on the development process and the risk of developing endocrine and reproductive disorders throughout human adult life.…”
Section: Environmental Factors Oxidative Stress and Adverse Prenatamentioning
confidence: 99%